The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpsyg.2020.00593
|View full text |Cite
|
Sign up to set email alerts
|

A Needs-Based Support for #MeToo: Power and Morality Needs Shape Women’s and Men’s Support of the Campaign

Abstract: The #MeToo campaign mobilized millions of women around the world to draw attention to the pervasiveness of sexual harassment. We conducted an online survey in Hungary (N = 10,293) immediately at the campaign's onset, and two subsequent studies in Israel and Germany (Ns = 356, 413) after it peaked, to reveal the motivations underlying people's support for, or criticism of the campaign. Integrating the assumptions of the needs-based model of reconciliation and system justification theory, we predicted and found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 64 publications
(83 reference statements)
0
20
0
1
Order By: Relevance
“…Consequently, they may ignore group disparities or perceive them as legitimate to defend their privileges (Uluğ & Tropp, in press). However, actual behavior promoting social justice may be contingent on the perceived illegitimacy of group disparities (Kende et al., 2020; Tropp & Uluğ, 2019). For instance, the recent debate on the #MeToo movement has led to a divide between men arguing that the #MeToo debate restricts what they could say/do and men standing up against the sexual harassment experienced by many women.…”
Section: Intergroup Contact and Collective Action Model For Advantagementioning
confidence: 99%
“…Consequently, they may ignore group disparities or perceive them as legitimate to defend their privileges (Uluğ & Tropp, in press). However, actual behavior promoting social justice may be contingent on the perceived illegitimacy of group disparities (Kende et al., 2020; Tropp & Uluğ, 2019). For instance, the recent debate on the #MeToo movement has led to a divide between men arguing that the #MeToo debate restricts what they could say/do and men standing up against the sexual harassment experienced by many women.…”
Section: Intergroup Contact and Collective Action Model For Advantagementioning
confidence: 99%
“…According to the latter model extended to intergroup contexts, when advantaged group members restore disadvantaged group members' sense of agency through their empowerment, this prevents passive acceptance of inequality and increases disadvantaged group members' readiness to act for change (Shnabel and Nadler 2015). In fact, the perception of #MeToo movement as empowering for women is positively associated with their campaign support (Kende, et al 2020). In contrast, the role of positive emotions in promoting social change has been questioned.…”
Section: Empowerment Anger and Women's Intention To Confrontmentioning
confidence: 99%
“…(2019), Kende, Nyúl, Lantos and colleagues (2020) found that gender system justification, meaning the motivation to justify current gender arrangements, is negatively associated with support for the #MeToo movement. Furthermore, women with lower gender system justification considered the movement to be more empowering, which in turn resulted in greater support for the movement (Kende et al ., 2020). However, neither Kunst and colleagues (2019) nor Kende and colleagues (2020) predicted perceptions of social‐sexual behavior.…”
Section: Introductionmentioning
confidence: 99%